Alpha-1 Antitrypsin Deficiency and Pulmonary Morbidity in Patients with Primary Immunodeficiency Disease: A Single-Center Experience. (27th May 2020) - Evers, Georg; Schulze, Arik Bernard; Thrull, Michael; Hering, Jan-Philipp; Schülke, Christoph; Wiewrodt, Rainer; Wittkowski, Helmut; Schmidt, Lars Henning; Mohr, Michael
Abstract : Background . Alpha-1 antitrypsin deficiency (AATD) is of importance in the pathogenesis of pulmonary emphysema, chronic obstructive pulmonary diseases (COPD), and bronchiectasis. Various pulmonary disorders are a typical feature of primary immunodeficiency disease (PID). This includes recurrent pulmonary infections, immunodysregulation, and autoinflammatory diseases. As a result, incidence of acute and chronic pulmonary diseases is higher. Interestingly, pulmonary morbidity in PID and AATD share similar features. To study the coexistence of AATD in patients suffering from PID, we performed the underlying investigation. Methods . We evaluated a study group of 149 patients ( n = 149) with PID. In total, serum AAT concentrations were available for 110 patients ( n = 110). For the identified patients, we analyzed both clinical associations and interactions. Results . Among the investigated patients, reduced serum AAT levels were detected in 7 patients. With regard to the genotype, PI∗ZZ was found in 2 patients, whereas PI∗MZ was observed in 5 patients. Independent of the underlying phenotype, obstructive lung diseases were found in 2 patients with PI∗ZZ and 2 patients with PI∗MZ. Conclusions . In Germany, the estimated percentage for PI∗ZZ and PI∗MZ is 0.01% and 1.9%, respectively. As demonstrated, the ratio in our study group was even higher. We identified seven patients with AATD. Since AATD contributes to pulmonary morbidity in PID patients, systematic underdiagnosis of the coexistence might yield a strong clinical impact. Hence, AAT analysis should be offered to all patients with confirmed PID diagnoses. To strengthen this finding, we suggest the investigation of larger databases.